PELAYANAN VISUM KLINIK DI RUMAH SAKIT AKDEMIK UNIVERSITAS GADJAH MADA SEJAK JANUARI 2013 HINGGA SEKARANG: SUATU LAPORAN KASUS - Pristianti, Raden Ajeng Kusparwati Ika; Widagdo, Hendro (Indonesian Journal of Legal and Forensic Sciences (IJLFS); Vol 2 (2012): Indonesian Journal of Legal and Forensic Sciences, 2012)
Rumah Sakit Akademik Universitas Gadjah Mada (RSA UGM) is a teaching hospital that recently began operating in March 2012. Currently the average number of patients per day who come in the clinic approximately 30 patients. As for the number of cases in the Emergency Room (ER) about 10 cases per day. For clinical visum requests are increased since the beginning of the year, especially for the case of traffic accidents and abuse. In the manufacture of clinical visum, RSA UGM still working with Sardjito hospital because Rumah Sakit Akademik have limited human resources. After observed in RSA UGM, clinical visum is still made in the absence of a standard operating procedure, both in terms of content and structure, as they found the involvement of leaders, although leaders are not involved in the process of handling victims. This happens because RSA has not been functioning as a teaching hospital, with no resident in the daily execution of which by the resident is expected to assist in the management of patients. While the number of cases that require a clinical visum, means indirectly have shown variations in the case of the hospital. Then RSA UGM should have started optimizing its function as an academic hospital with start receiving co ass and resident. In the manufacture of clinical visum at UGM academic hospital, is still required supervision and assistance, especially from those who are more competent and experienced, in this case dr. Sardjito hospital. Expected some time, academic hospitals can be self-sufficient in the manufacture of clinical visum.
Keywords: clinical visum, RSA, co ass, resident